The Macroeconomics of Scaling Up Aid : The Gleneagles Initiative for Benin - Mongardini, Joannes (IMF Working Papers; Working Paper ;, 2009)
This paper assesses the macroeconomic implications of scaling up aid for Benin in line with the Gleneagles commitment to double aid to poor countries over the next three years to reach USD 85 per capita by 2010 and keep it at that level thereafter. The analysis suggests that the additional aid inflows can be accommodated under Fund-supported programs without major disruptions to macroeconomic stability, provided the inflows are highly concessional and used effectively. There are, however, significant risks that the impact on growth and poverty reduction of the additional aid inflows could fall short of expectations, given Benin's limited absorptive and administrative capacity.